2021
DOI: 10.1038/s41398-021-01231-y
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omic and multi-species meta-analyses of nicotine consumption

Abstract: Cross-species translational approaches to human genomic analyses are lacking. The present study uses an integrative framework to investigate how genes associated with nicotine use in model organisms contribute to the genetic architecture of human tobacco consumption. First, we created a model organism geneset by collecting results from five animal models of nicotine exposure (RNA expression changes in brain) and then tested the relevance of these genes and flanking genetic variation using genetic data from hum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
0
14
1
Order By: Relevance
“…Many researchers have begun to tackle the issue of variant prioritization by integrating multiple sources of information 72‐74 . Indeed, most GWAS include detailed post‐hoc analyses toward the identification of credible causal variants.…”
Section: Theme A: Bridging the Gap Between Human And Animal Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…Many researchers have begun to tackle the issue of variant prioritization by integrating multiple sources of information 72‐74 . Indeed, most GWAS include detailed post‐hoc analyses toward the identification of credible causal variants.…”
Section: Theme A: Bridging the Gap Between Human And Animal Researchmentioning
confidence: 99%
“…Studies of alcohol and cannabis use disorders have shown quantitative and qualitative differences between the genetics of consumption quantity and frequency and the genetics of the disorders (e.g., impaired functioning, physical dependence, disruption of social responsibilities) 12,86 . Likewise, a geneset derived from tobacco exposure paradigms in rodents shows modest enrichment for the SNP‐heritability of human tobacco consumption 87 . Notably, inbred strain comparison/selective breeding studies have allowed scientists to examine the effects of genetic background on multiple related traits 88 .…”
Section: Theme A: Bridging the Gap Between Human And Animal Researchmentioning
confidence: 99%
See 3 more Smart Citations